2021
DOI: 10.1111/php.13573
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the Potential of Ru(II) Dual‐action Compounds with the Power of the Heavy‐atom Effect

Abstract: We report the synthesis, photochemical and biological characterization of two new Ru(II) photoactivated complexes based on [Ru(tpy)(Me 2 bpy)(L)] 2+ (tpy = 2,2':6',2''terpyridine, Me 2 bpy = 6,6'-dimethyl-2,2'-bipyridine), where L = pyridyl-BODIPY (pyBOD). Two pyBOD ligands were prepared bearing flanking hydrogen or iodine atoms. Ru(II)bound BODIPY dyes show a red-shift of absorption maxima relative to the free dyes and undergo photodissociation of BODIPY ligands with green light irradiation. Addition of iodin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…In 2021, N. Toupin et al proposed to link a ruthenium PPG with the pyridyl-BODIPY photosensitizer, which has a high quantum yield of singlet oxygen ( Figure 14 ) [ 78 ]. Upon irradiation with green light (λ = 520–530 nm) for 15 min at an energy density of 50 J/cm 2 , the pyridyl-BODIPY ligand 15 was liberated from the conjugate 13 .…”
Section: Photoactivated Chemotherapy (Photocleavable Groups)mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2021, N. Toupin et al proposed to link a ruthenium PPG with the pyridyl-BODIPY photosensitizer, which has a high quantum yield of singlet oxygen ( Figure 14 ) [ 78 ]. Upon irradiation with green light (λ = 520–530 nm) for 15 min at an energy density of 50 J/cm 2 , the pyridyl-BODIPY ligand 15 was liberated from the conjugate 13 .…”
Section: Photoactivated Chemotherapy (Photocleavable Groups)mentioning
confidence: 99%
“…The authors also demonstrated that the released ruthenium complex 12 could inhibit the mitogen-activated protein kinase signaling pathway characteristic of tetrahydrocurcumin, thereby exerting an anticancer effect. In 2021, N. Toupin et al proposed to link a ruthenium PPG with the pyridyl-BODIPY photosensitizer, which has a high quantum yield of singlet oxygen (Figure 14) [78]. Upon irradiation with green light (λ = 520-530 nm) for 15 min at an energy density of 50 J/cm 2 , the pyridyl-BODIPY ligand 15 was liberated from the conjugate 13.…”
Section: -640mentioning
confidence: 99%
“…Any agent that requires a very high light dose in monolayer cell culture is unlikely to have much relevance in vivo. There are reports that indicate light doses as high as 50-100 J sq cm À1 for use in monolayer studies (27,28). Such agents are unlikely to be useful for clinical purposes, or even for eradicating cells in 3D culture where light doses are typically greater than what is required when dealing with only monolayers.…”
Section: Pdt Efficacy and Selectivitymentioning
confidence: 99%
“…While many photoactivated Ru­(II) complexes have been designed to display red-shifted absorption windows with high extinction coefficients, they generally feature π-extended ligands that reduce their solubility in aqueous media, organic chromophores that are responsible for its photosensitization properties, or nanoparticles that incorporate many Ru­(II) molecules. Moreover, in attempts to shift Ru­(II) complexes to the therapeutic window, the PCT mode is sacrificed for PDT capabilities; therefore, only a handful of dual PCT/PDT agents can be activated with green or red light. In our synthetic design, we utilized an intermediate aldehyde that can be subjected to facile oxime formation via a “click” reaction to efficiently produce conjugates with green light activated dual action PCT/PDT analogs . The Ru PCT/PDT-cathepsin inhibitor conjugate prepared by this method efficiently inactivates purified cathepsins B and L both upon irradiation and when kept in the dark.…”
Section: Introductionmentioning
confidence: 99%